Total neoadjuvant chemotherapy according to the FOLFIRINOX regimen for locally advanced adenocarcinoma of the stomach and cardioesophageal junction: interim results - M. V. Sedova; M. A. Batov; A. A. Kolomeytseva; V. M. Khomyakov; N. N. Volchenko; A. A. Fedenko (Исследования и практика в медицине)
Purpose. To study the eﬃcacy and safety of total neoadjuvant chemotherapy (NACT) with the FOLFIRINOX regimen for locally advanced gastric (GC) and cardioesophageal junction (CEJ) cancer.Patients and methods. Patients with histologically conﬁrmed locally advanced gastric adenocarcinoma and CEJ, clinical stage cT3 or higher and/or regional lymph node involvement (cN+), without evidence of distant metastasis were included in our open-label, single-centre, non-randomised study. In the FLOT control group, patients received 4 courses preoperatively and 4 postoperatively with follow-up. I In the FOLFIRINOX group 8 courses of chemotherapy were administered in neoadjuvant mode, followed by surgery and observation. The tumor regression grade was assessed in accordance with Becker, Mandard and G. A. Lavnikova scales.Results. The study included 136 patients, 119 of whom started treatment according to the protocol (ITT population). Fiﬅy-nine patients were enrolled into the FLOT group and 60 into the FOLFIRINOX group. One-year progression-free survival (PFS) was 67,5 % in the FLOT group and 90,4 % in the FOLFIRINOX group (p = 0,29). The estimated 2-year PFS in the FLOT group was 61,4 % [95 % CI, 48,4–77,9 %]. Median PFS and overall survival (OS) were not reached. The incidence of events (progression or death) was lower in the FOLFIRINOX group (odds ratio [OR] 0,40 [95 % CI 0,16–0,97, p = 0,047]). Adverse prognostic factors regardless of treatment were lymphatic (L1), vascular (V1) and perineural invasion (Pn1), and regional lymph node involvement aﬅer chemotherapy (ypN+) [p = 0,046; p = 0,014; p = 0,0021; p = 0,04, respectively]. There was no correlation between pathological complete response and survival rates.Conclusion. Total neoadjuvant chemotherapy with the FOLFIRINOX regimen for locally advanced GC/ CEJ demonstrated comparable to the perioperative FLOT one-year PFS rate. No association was found between tumor regression grade and survival outcomes.